PENGARUH PROGRAM SENSUS PAJAK NASIONAL TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA MALANG - ia, Shof (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aim to analyze influence of tax national census toward of tax compliance of individual taxpayers in Malang City. This research was quantitative descriptive research. The collected of data used questionnaire as instrument. The respondents of this research are individivual taxpayers in Malang City, especially independent business owners who have sticker Sensus Pajak Nasional. Simple linear regression analysis method used to analyze variable on this research, tax national census and individual taxpayer’s compliance which of proxy into tax awareness, tax morale, tax paying commitment, understanding of tax, and fairness distribution of tax. The results of this study indicate that tax national census gived a significant positive impact to taxpayer’s compliance, especially individual taxpayers. Keywords: national tax census, taxpayer’s compliance, individual taxpayers